Speciation and cycling of iodine in the subtropical North Pacific Ocean - Ştreangă, Iulia-Mădălina; Repeta, Daniel J.; Blusztajn, Jerzy S.; Horner, Tristan J. (Frontiers in Marine Science, 2024)
Iodine intersects with the marine biogeochemical cycles of several major elements and can influence air quality through reactions with tropospheric ozone. Iodine is also an element of interest in paleoclimatology, whereby iodine-to-calcium ratios in marine carbonates are widely used as a proxy for past ocean redox state. While inorganic iodine in seawater is found predominantly in its reduced and oxidized anionic forms, iodide (I−) and iodate (IO3−), the rates, mechanisms and intermediate species by which iodine cycles between these inorganic pools are poorly understood. Here, we address these issues by characterizing the speciation, composition and cycling of iodine in the upper 1,000 m of the water column at Station ALOHA in the subtropical North Pacific Ocean. We first obtained high-precision profiles of iodine speciation using isotope dilution and anion exchange chromatography, with measurements performed using inductively coupled plasma mass spectrometry (ICP-MS). These profiles indicate an apparent iodine deficit in surface waters approaching 8% of the predicted total, which we ascribe partly to the existence of dissolved organic iodine that is not resolved during chromatography. To test this, we passed large volumes of seawater through solid phase extraction columns and analyzed the eluent using high-performance liquid chromatography ICP-MS. These analyses reveal a significant pool of dissolved organic iodine in open ocean seawater, the concentration and complexity of which diminish with increasing water depth. Finally, we analyzed the rates of IO3− formation using shipboard incubations of surface seawater amended with 129I−. These experiments suggest that intermediate iodine species oxidize to IO3− much faster than I− does, and that rates of IO3− formation are dependent on the presence of particles, but not light levels. Our study documents the dynamics of iodine cycling in the subtropical ocean, highlighting the critical role of intermediates in mediating redox transformations between the major inorganic iodine species.